Taqyim Qillati al- Ihtimam Thulab al-Fashli E fi Qismi Ta’lim al-Lughah al-‘Arabiyyah bi al-Ta’lim ‘ala al-Tahshil ad-Dirasi - Ailsa Aulia (AlFaqrah: Journal of Arabic Studies, 2026)
AbstractThis study aims to analyze the influence of self-esteem and self-concept on the low level of students’ interest in learning. Interest in learning is one of the important factors that affects educational success and the quality of human resources. A low interest in learning can lead to decreased motivation and understanding of learning materials, as well as lower quality of students’ learning outcomes. This study uses a qualitative method based on literature review and interviews. The data were obtained through the review of various relevant journals, books, and scientific articles, as well as interviews with Class E students of the Arabic Language Education Department, class of 2024, to understand their perspectives and experiences regarding self-motivation and interest in learning. This research was conducted over approximately two weeks. The results showed that self-confidence and self-concept have a significant influence on students’ interest in learning. Students who possess self-confidence and a positive understanding of themselves tend to be more active, motivated, and interested in participating in the learning process. On the other hand, low self-confidence and self-concept cause students to feel incapable, lack confidence, and fail to recognize their own potential, which ultimately decreases their desire to learn. This study emphasizes the importance of strengthening self-confidence and self-concept as an effort to increase students’ interest in learning and improve the overall quality of education.